2017
DOI: 10.1038/leu.2017.335
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic thresholds for free light chains in multiple myeloma depend on the assay used

Abstract: Leukemia accepted article preview online, 20 November 2017. doi:10.1038/leu.2017.335.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…10,15 The k/l ratio is higher for Freelite than N Latex for values >1 (by Freelite), as we reported previously. 15 As FLC measurement is increasingly important in the diagnosis and monitoring of paraprotein-related kidney diseases, we were particularly interested to analyze the effect of kidney dysfunction on the 2 available FLC assays. In both assays, k and l FLC correlate inversely with eGFR, but this effect is more pronounced in l FLC measurement by N Latex.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…10,15 The k/l ratio is higher for Freelite than N Latex for values >1 (by Freelite), as we reported previously. 15 As FLC measurement is increasingly important in the diagnosis and monitoring of paraprotein-related kidney diseases, we were particularly interested to analyze the effect of kidney dysfunction on the 2 available FLC assays. In both assays, k and l FLC correlate inversely with eGFR, but this effect is more pronounced in l FLC measurement by N Latex.…”
Section: Discussionsupporting
confidence: 85%
“…As reported previously, k FLCs are in general higher by Freelite than by N Latex. 15 In contrast, l FLCs are higher by N Latex. 10,15 The k/l ratio is higher for Freelite than N Latex for values >1 (by Freelite), as we reported previously.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…So far, only a limited number of comparison studies between the different assays exist. Previous comparisons between N Latex and Freelite assay [14][15][16][17][18][19] and between Sebia FLC and Freelite assay 13,20,21 have shown discrepancies in determination of light-chain values and κ/λ ratio. In comparison analyses between Freelite and N Latex FLC, and between Freelite and Sebia FLC, absolute FLC concentrations measured by Sebia FLC or N Latex FLC were lower compared with Freelite.…”
Section: Introductionmentioning
confidence: 95%
“…Two recently published studies showed that the diagnostic thresholds for iFLC/niFLC ratio ≥ 100 proposed for Freelite do not apply to N Latex FLC and Sebia FLC. New thresholds for N Latex FLC (iFLC/niFLC ratio ≥ 30) and for Sebia FLC (iFLC/niFLC ratio ≥ 16) were proposed 14,20 . This is very important clinically because, due to different results of FLC assays, patients may not be detected as MM patients requiring treatment, responses might not be evaluated consistently, and treatment decisions may be "test-dependent" and not truly disease dependent.…”
Section: Introductionmentioning
confidence: 99%